Participation in Physical Activity and Sport of the LGBT Community - Buitrago-Camacho, Karen-Tatiana (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In this article different topics will be addressed to understand, understand and situate the LGBTI community in terms of physical activity and sport, based on the different studies that were analyzed both nationally and internationally, in recent years. From this review the perspectives and meanings of people regarding the theme or central axis of this article, can vary according to various factors such as: Age, profession, context, sex, and sports level, among others. This is why, while some people have negative attitudes and biases in relation to sexual diversity, other studies also show a positive change towards LGBTI sexual minorities thanks to theoretical enrichment and recognition of this community by institutions social, political, and cultural. On the other hand, it can be concluded that today the sports field continues to be strongly rooted in heterosexist thoughts that delimit the participation of this group, however, it should be noted that a positive change is already observed on the part of different organizations, materialized by the recognition and acceptance of the participation of LGBTI people, in the sports context, as an essential part of their free development.